CHINA’S SOFT POWER: THE MAKING OF FOOTBALL SUPERPOWER - Santosa, Ganjar Ariel (Jurnal Pertahanan dan Bela Negara, 2017)
Abstract – A significant economic rise provides an opportunity for China to expand its influence globally, especially in sectors where China does not have strong influences. One of them is football. The average achievement of its National football has pushed the government to implement soft power strategy to improve the quality and the competitiveness of its national football. This strategy is carried out with a strong synergy between the government and private sector businesses nationwide. This paper will analyze how China’s soft power strategy implemented in order to advance its national football and their national pride globally. Keywords: China, soft power, economy, football, investment